Knowledge Integration in Contemporary Islamic Education: Efforts to Eliminate the Dichotomy Between Religious and General Sciences - Haniefah Iqtianti; Melli Indah Novitasari; Muhammad Agung Prabowo; Muhammad Iqbal (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to examine the concept of knowledge integration in contemporary Islamic education as an effort to eliminate the dichotomy between religious and general sciences. This research employs a qualitative method with a library research approach. Data sources were obtained from books, scientific journals, articles, and various references relevant to the research topic. Data collection techniques were conducted through documentation and literature review, while data analysis utilized descriptive qualitative analysis. The findings indicate that knowledge integration in contemporary Islamic education is an effort to unify religious and general sciences so that they can develop in a balanced manner. The concept of knowledge integration has been developed through the ideas of scholars such as Syed Muhammad Naquib Al-Attas and Ismail Raji Al-Faruqi, who emphasized the importance of the Islamization of knowledge. In addition, the integration-interconnection model (Spider Web) represents one form of knowledge integration that connects various academic disciplines with Islamic values. The implementation of knowledge integration within the Islamic Religious Education (PAI) curriculum can be achieved by linking religious teachings with real-life situations, science, technology, and contextual learning. Through knowledge integration, students are expected to develop a balance between intellectual, spiritual, and social competencies, thereby minimizing the dichotomy between religious and general sciences in contemporary Islamic education.